Diversity and potential uses of legumes as animal feed in Zimbabwe - Alfred Maroyi (Veterinary Research Notes)
This review provides an appraisal of the legume species that have been documented as animal feed in Zimbabwe. Multiple searches on existing literature on the legumes used as animal feed in Zimbabwe were conducted in online databases such as Scopus®, Google Scholar, SpringerLink®, SciELO, ScienceDirect®, PubMed®, and Web of Science, as well as using pre-electronic literature sources obtained from the university library. This study recorded 86 species that are used as fodder, forages, and pastures in Zimbabwe, and 27.9% of these species are exotic, either naturalized as weeds or cultivated in agricultural fields or home gardens. Major genera with at least two species used as animal feed in Zimbabwe include Albizia, Arachis, Brachystegia, Desmodium, Leucaena, Ormocarpum, Pterocarpus, Senegalia, Sesbania, Stylosanthes, Trifolium, and Vachellia. Trees (61.6%), followed by herbs (22.1%), are the primary sources of animal feed in Zimbabwe. These research findings contribute valuable literature about the value of legumes in meeting nutrient needs and maintaining the productivity of livestock populations. [Vet. Res. Notes 2024; 4(11.000): 100-107]